CHALLENGES IN IMPLEMENTING STUNTING PREVALENCE REDUCTION POLICIES: INTEGRATING UPSTREAM AND DOWNSTREAM APPROACHES - Zainul Fahrudin; Sri Roekminiati; Sri Kamariyah (International Journal of Multidisciplinary Reseach, 2026)
Stunting remains a chronic nutritional problem that remains unresolved despite declining national prevalence, as aggregate reductions do not guarantee integrated interventions at the family level. The main problem of this study is the implementation gap between policy design and field outcomes, particularly the weak integration of upstream approaches in the form of sensitive interventions and downstream approaches in the form of specific interventions. The study aims to analyze the challenges of implementing policies to reduce stunting prevalence and the factors inhibiting upstream-downstream convergence in Malang Regency, East Java. The study used a qualitative approach with a case study type. The study population was stakeholders involved in policy implementation, while the sample was determined purposively with twelve informants including actors at the district level, community health centers, villages, field implementers, and target families. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive model of data reduction, data presentation, and conclusion drawing guided by Edwards III and Grindle's implementation theory. The validity was tested through triangulation. The results showed that the main challenge was not the absence of a program, but rather weak data harmonization, limited resources, fragmented bureaucratic structures, and disconnected referrals between downstream services and upstream interventions in target households. It was concluded that stunting reduction requires an integrated case resolution mechanism through a shared target list, a cross-sector follow-up matrix, and local case managers so that each household receives a complete service package.